2016
DOI: 10.1080/23809000.2017.1271981
|View full text |Cite
|
Sign up to set email alerts
|

Treating nicotine dependence and preventing smoking relapse in cancer patients

Abstract: Introduction Despite the well-documented harmful effects of smoking, many cancer patients continue to smoke. Smoking cessation is critical to address in this population given the associated increase in treatment toxicity, risk of second primary tumors, decrease in treatment response and higher disease-specific and all-cause mortality with continued smoking following a cancer diagnosis. This review seeks to summarize the latest recommendations and guidelines on smoking cessation treatment for patients diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 129 publications
(258 reference statements)
0
22
1
Order By: Relevance
“…These structural changes may have contributed to increased reach by providing more flexible treatment options aligned with patient preferences, and by reducing barriers for oncology clinicians to connect patients with available cessation treatment or provide said treatment themselves. 26,27 Some good news is that there was little evidence of reach inequities among several of the demographic groups assessed, with reach being largely equivalent at both Time 1 and 2 among black/African American, white, Hispanic, and non-Hispanic individuals. Although differences in reach among these groups did not achieve statistical significance, likely due to the low sample size of 22 settings, reach increased meaningfully.…”
Section: Discussionmentioning
confidence: 99%
“…These structural changes may have contributed to increased reach by providing more flexible treatment options aligned with patient preferences, and by reducing barriers for oncology clinicians to connect patients with available cessation treatment or provide said treatment themselves. 26,27 Some good news is that there was little evidence of reach inequities among several of the demographic groups assessed, with reach being largely equivalent at both Time 1 and 2 among black/African American, white, Hispanic, and non-Hispanic individuals. Although differences in reach among these groups did not achieve statistical significance, likely due to the low sample size of 22 settings, reach increased meaningfully.…”
Section: Discussionmentioning
confidence: 99%
“…The US Surgeon General concluded that a causal relationship exists between continued tobacco use among cancer patients and poor clinical outcomes, including cancer-specific mortality, an increased risk of disease recurrence, and decreased response to cancer treatment [ 1 ]. Despite these risks, upwards of 50% of those who were smokers when diagnosed continue to smoke or relapse soon after receiving their diagnosis [ 2 , 3 ]. Identifying effective smoking cessation interventions for cancer patients is therefore a priority [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying effective smoking cessation interventions for cancer patients is therefore a priority [ 4 ]. This requires identifying correlates of smoking behavior, which can serve as intervention targets [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of this finding, we suggest a team approach to cessation care where oncologists may be the first to engage with the patient regarding the need for cessation, providing for example; brief motivational advice with information about the individualised benefits of quitting, and formulation of an agreed plan with the patient on the most appropriate referral and support strategy. This should be followed by engagement with adequately resourced, accessible health professionals who understand both cancer treatment and smoking cessation . Multiple practice models could be developed to meet these requirements.…”
Section: Discussionmentioning
confidence: 99%